How gamification boosts learning in STEM higher education: a mixed methods study - Margarita Ortiz-Rojas; Katherine Chiluiza; Martin Valcke; Cindy Bolanos-Mendoza (International Journal of STEM Education)
Abstract Background The demand for professionals with expertise in Science, Technology, Engineering, and Mathematics (STEM) continues to grow. To meet this demand, universities are actively seeking strategies to engage more students in STEM disciplines and improve their learning outcomes. One promising approach is gamification, specifically using leaderboards. This study investigates the impact of leaderboard-based gamification on the learning performance of 175 students in a calculus course, with a focus on the mediating roles of autonomous motivation and self-efficacy, as well as potential moderating factors such as gender and gaming experience. A mixed-method research approach was employed, combining a pretest–posttest quasi-experimental design with nine qualitative interviews. Results A significant improvement in learning performance for students in the gamified condition was observed. However, no significant effects were found related to the mediating variables. Qualitative analysis supported these findings, revealing that students did not perceive an increase in autonomy within the gamified condition, and instead, themes of controlled motivation were prevalent. While the leaderboard provided a sense of achievement for most participants, the quantitative analysis did not show a strong correlation between self-efficacy and learning performance. Conclusions This study suggests that leaderboard-based gamification can enhance learning performance in calculus courses at the university level. However, the findings highlight the importance of careful gamification design, particularly in how different game elements influence students' motivational aspects.